2023
DOI: 10.1186/s12872-023-03277-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body mass index on clinical outcomes after robotic cardiac surgery: is there an obesity paradox?

Abstract: Background To investigate the effect of body mass index (BMI) on clinical outcomes after robotic cardiac surgery, and to explore the postoperative obesity paradox. Methods The data of 146 patients who underwent robotic cardiac surgery under cardiopulmonary bypass (CPB) from July 2016 to June 2022 in Daping Hospital of Army Medical University were retrospectively analyzed, and their demographic data and related clinical data were statistically analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…In our study, similar to the results of Wu et al (7), the duration of intubation, ICU stay, and hospital stay in the OBMI patient group was significantly longer than that of all other groups. Apart from all these, postoperative surgical revision and even mortality rates were similar in all groups.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, similar to the results of Wu et al (7), the duration of intubation, ICU stay, and hospital stay in the OBMI patient group was significantly longer than that of all other groups. Apart from all these, postoperative surgical revision and even mortality rates were similar in all groups.…”
Section: Discussionsupporting
confidence: 91%
“…While at first glance, the operative and postoperative data of obese patients were expected to be poor, many studies conducted on obese patients showed that the results were much better, and they termed this phenomenon "the obesity paradox" (4). After the emergence of this idea, many articles were written on this subject, and it was reported in these articles that such a paradox did not exist and that the results were worse in obese patients (7,8). While the issue of obesity has been examined many times in scientific research, the situation of patients with lower-than-normal BMI has been somewhat overlooked, especially in cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation